1997
DOI: 10.1076/ceyr.16.4.339.10684
|View full text |Cite
|
Sign up to set email alerts
|

Stromal fibroblasts are associated with collagen IV in scar tissues of alkali-burned and lacerated corneas

Abstract: The enhanced expression of collagen IV by the fibroblastic cells in the stroma of injured corneas is consistent with the notion that they may contribute to the formation of basal lamina-like structures in injured corneas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…They fail to repair damaged corneal stroma, although they proliferate and assume myofibroblast phenotypes of scar tissue. 13–15 In addition, there is a lack of definitive marker(s) that can aid the identification of MSC. 6 However, cell surface markers that are characteristic of MSC have been reported and are associated with the identity of MSC; for example CD44, CD105, CD73, and CD90, but not CD45, CD19, CD79, CD14, CD11b or HLA-DR.…”
Section: Introductionmentioning
confidence: 99%
“…They fail to repair damaged corneal stroma, although they proliferate and assume myofibroblast phenotypes of scar tissue. 13–15 In addition, there is a lack of definitive marker(s) that can aid the identification of MSC. 6 However, cell surface markers that are characteristic of MSC have been reported and are associated with the identity of MSC; for example CD44, CD105, CD73, and CD90, but not CD45, CD19, CD79, CD14, CD11b or HLA-DR.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated deposition of collagen IV in rabbit corneal stroma injured by alkali burns or lacerations, and its association with fibroblast activation and scar tissue [20,21]. Similarly, α-SMA expression is the hallmark for myofibroblast differentiation, the cells responsible for stromal haze and scarring [12,22].…”
Section: Discussionmentioning
confidence: 97%
“…Deposition of Coll-IV was also found in rabbit corneal stroma injured by alkali burns or laceration, was associated with activated stromal fibroblasts, and was thought to be the reason for forming opaque granulation tissue. 7 In the early stage of wound healing, fibronectin exudated from the plasma or tears and secreted by activated fibroblasts is deposited in the corneal stroma as a provisional matrix. Fn is completely reabsorbed when the wound healing process is completed.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we analysed the expression of collagen IV (Coll-IV), a basement membrane component, which is expressed by injured corneal stromal fibroblasts. 7 We also studied fibronectin (Fn), a provisional matrix component, which is expressed by stromal fibroblasts during early and active wound healing. 8 Furthermore, we determined whether fibroblasts expressed a-smooth muscle actin (a-SMA), a marker of myofibroblasts, 9 responsible for corneal wound contraction.…”
mentioning
confidence: 99%